Demystifying integrated power and desalination processes evaluation based on standard primary energy approach. (1st January 2022) - Shahzad, Muhammad Wakil; Ng, Kim Choon; Burhan, Muhammad; Chen, Qian; Jamil, Muhammad Ahmad; Imtiaz, Nida; Xu, Ben Bin
Highlights: Common platform for assorted processes comparison. Current separation processes operating only at 10-13% of thermodynamic limit. Standard primary energy approach demystifies the qualitative aspect of derived energy. Over 30% performance level need to achieve for future sustainability. Hybrid MEDAD cycle has highest performance, 20% of TL. Abstract: The energy efficiency of seawater desalination processes is usually expressed in terms of kWh electricity or low-grade heat per cubic meter of water produced. This energy efficiency evaluation criteria unfortunately omitted the embedded quality of derived energy input. To have fair comparison of assorted desalination processes, it is important to consider quantity as well as quality of derived energy input based on their generation mechanisms. The numerator (m 3 of distillate produced) and denominator (kWh_derived energy consumption) terms in energy efficiency evaluation are to be benchmark onto a common platform for fair evaluation and comparison. An inadequate comparison may result in an inferior adaptation of desalination methods that can lead to high economical destruction. In this article, a detailed thermodynamic framework has been developed to convert cogeneration-based electricity and heat into standard primary energy input. The proposed standard primary energy platform will help to demystify the quality and quantity aspects of derived energy supply. The thermodynamic based rigorous calculations show that 1.813 units of primary energy are required to produce one unit of electricity due to conversion efficiencies and loses involved in the power plant. On the other hand, one unit low-pressure steam to operate thermally driven desalination cycles need only 0.0944 units of primary energy. This stark difference clearly shows that omitting the grade of energy in performance evaluation can lead to an in-efficient installation decision. This proposed framework will provide a basic ground for future efficient processes selection and assorted processes evaluation at common platform.